2012
DOI: 10.1093/icesjms/fss158
|View full text |Cite
|
Sign up to set email alerts
|

Atlantic cod (Gadus morhua) feed during spawning off Newfoundland and Labrador

Abstract: We test a current assumption that Atlantic cod (Gadus morhua) off Newfoundland and Labrador, Canada, do not feed during the protracted spawning season (March-September). Stomach contents were analysed from 10 473 cod from four Northwest Atlantic Fisheries Organization regions (2J, 3K, 3L, and 3Ps) over 9 years from which gonads were also analysed to determine sex and maturity status. Adult cod in spawning condition did feed in all regions, usually at rates equivalent to or even greater than non-spawning fish a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(20 citation statements)
references
References 32 publications
6
14
0
Order By: Relevance
“…10). This is consistent with reports of low growth, somatic condition, liver index and age-at-maturity associated with diets dominated by Pandalus shrimp (Sherwood et al 2007, Krumsick & Rose 2012. The distribution of the somatic condition curves was more leptokurtic as time progressed (Fig.…”
Section: Capelin Availability As a Driversupporting
confidence: 91%
See 1 more Smart Citation
“…10). This is consistent with reports of low growth, somatic condition, liver index and age-at-maturity associated with diets dominated by Pandalus shrimp (Sherwood et al 2007, Krumsick & Rose 2012. The distribution of the somatic condition curves was more leptokurtic as time progressed (Fig.…”
Section: Capelin Availability As a Driversupporting
confidence: 91%
“…We therefore ex pected that the changes in capelin biology and ecology that took place during the 1990s, and most importantly its severe abundance decline, must have represented a serious burden. Northern cod's diet composition changed from a heavy reliance on capelin during the 1980s and early 1990s to a reliance more on Pandalus shrimp, prey with a much lower energy density, during the late 1990s and 2000s; this shift was more marked in the northern regions (Dawe et al 2012, DFO 2012, Krumsick & Rose 2012. We used Lambert's (2011Lambert's ( , 2012 simple linear regression relating Atlantic cod's somatic condition during January to somatic condition during May in the northern Gulf of St. Lawrence to convert fall to spring somatic condition (when it is at its minimum), which allowed us to compare spring condition to threshold values found in starvation and feeding experiments (Lambert & Dutil 1997).…”
Section: Capelin Availability As a Drivermentioning
confidence: 99%
“…Of note, there were fewer capelin in these northern channels than in the Bonavista Corridor as a consequence of the decline and southward distribution shift of capelin in the early 1990s (Frank et al 1996). Subsequent feeding by cod on capelin was almost nil in the north (Krumsick and Rose 2012). Meanwhile, the Bonavista Corridor group increased to over 200 000 t; hence, it is possible that some of the Bonavista Corridor fish moved north to seed the groups in the Notre Dame Channel and Hamilton Bank -Hawke Channel.…”
Section: Discussionmentioning
confidence: 91%
“…Capelin virtually disappeared north of the Bonavista Corridor in the early 1990s (Frank et al 1996;DFO 2015a). In the Bonavista Corridor, capelin remained in reduced numbers when the stock was at its lowest, and cod diet reflected that (e.g., Krumsick and Rose 2012). In recent years, anecdotal evidence suggests capelin have returned to the north, although no surveys have been done.…”
Section: Discussionmentioning
confidence: 99%
“…A decline in feeding is often seen during the reproductive stages of fish (Krumsick and Rose 2012;Ozyurt et al 2012), and sometimes can be observed in both sexes (Fordham and Trippel 1999;Skjaeraasen et al 2004). Good nutrition and ample food for the mother fish is essential to developing greater energy reserves during early stages of egg formation; therefore, females tend to continue feeding as they approach spawning (Skjaeraasen et al 2004) or start feeding sooner after spawning than do male fish and consume more food than males (Fordham and Trippel 1999).…”
Section: Delta Smeltmentioning
confidence: 99%